Financial Literacy and Investment Decision-Making Among Salaried and Non-Salaried Individuals: An Empirical Analysis - Tanuja Singh, Vaibhav Sukhwal (Journal of Informatics Education and Research, 2025)
Financial literacy has become a central determinant of economic well-being, shaping how individuals manage resources, select investment avenues, and prepare for future financial obligations. Despite increasing financial inclusion initiatives, many individuals—particularly in developing economies—continue to demonstrate limited understanding of essential financial concepts, leading to suboptimal financial decisions and heightened exposure to financial vulnerabilities. This study examines the financial literacy levels and investment behavior of salaried and non-salaried individuals in the Ajmer district using the OECD financial literacy framework. A structured questionnaire was administered to 465 respondents selected through multistage random sampling. Findings reveal moderate yet uneven financial literacy across demographic groups, with salaried individuals exhibiting more stable and conservative investment behavior compared to the relatively risk-tolerant non-salaried segment. Education, occupation, income stability, and household size emerged as significant determinants of financial literacy and investment choices. The study emphasizes the need for targeted financial education initiatives tailored to demographic characteristics to promote responsible financial decision-making and long-term financial well-being.